Is cachexia associated with chemotherapy toxicities in gastrointestinal cancer patients? A prospective study. Issue 2 (28th March 2019) - da Rocha, Ilanna Marques Gomes; Marcadenti, Aline; de Medeiros, Galtieri Otávio Cunha; Bezerra, Ricardo Andrade; Rego, Juliana Florinda de Mendonça; Gonzalez, Maria Cristina; Fayh, Ana Paula Trussardi
Abstract: Background: Chemotherapy is an effective treatment with good clinical response in patients with cancer. However, it can cause exacerbated toxicities in patients and consequently change the course of treatment. Some factors may interfere with this toxicity such as body composition, especially in gastrointestinal cancer. The aim of this study was to evaluate the effects of body composition, nutritional status, and functional capacity scale in predicting the occurrence of toxicities in gastrointestinal cancer patients during chemotherapy treatment. Methods: This is a prospective study with gastrointestinal cancer patients at the beginning of chemotherapy treatment. Sarcopenia and muscle attenuation were assessed using the skeletal muscle index from computerized tomography by measuring cross‐sectional areas of the L3 tissue (cm 2 /m 2 ). Cachexia was graded according to involuntary weight loss associated with sarcopenia. Nutritional status was assessed by using anthropometric evaluation and Patient‐Generated Subjective Global Assessment. Functional capacity was evaluated by handgrip strength and Eastern Cooperative Oncology Group (ECOG) Performance Status scale. Haematological gastrointestinal and dose‐limiting toxicities (DLTs) were defined according to National Cancer Institute Common Toxicity Criteria. The associations among sarcopenia, cachexia, nutritional status, and functional capacity with DLT were assessed by univariate and multivariate Cox regression model. Results: A total of 60 patients were evaluated (55% male, 60.9 ± 14.0 years) and followed up for a mean of 55 days. Most patients had normal weight (44.2%) and good ECOG Performance Status (≤1) at baseline (78%). During the chemotherapy period, the most prevalent toxicities were diarrhoea, nausea, and anorexia, but the presence of DLT was similar between cycles ( P > 0.05). Cachexia was associated with a higher toxicity manifested by diarrhoea ( P = 0.02), nausea ( P = 0.02), and anorexia ( P < 0.01 and P = 0.03 at Cycles 1 and 2, respectively). Sarcopenic and cachetic individuals experienced more toxicities and DLT during chemotherapy. The only factors associated with DLT in the multivariate Cox regression analyses including the presence of metastasis and the chemotherapy protocol were cachexia and the ECOG scale ( P < 0.001 for both). Conclusions: Cachexia and ECOG score may identify patients with an increased risk for developing severe toxicity events during chemotherapy treatment for gastrointestinal cancer.